2021
DOI: 10.1590/0100-29452021113
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and production of coconut palm cultivated with mineral fertilization in the state of Pará

Abstract: Fertilization greatly affects coconut productivity; nevertheless, information on crop nutrition is relatively scarce for coconut in the state of Pará, Brazil. This study evaluated the effect of fertilization with nitrogen (N), phosphorus (P), potassium (K), and magnesium (Mg) on the nutritional status and coconut yield under the edaphoclimatic conditions of the municipality of Moju, Pará State (Brazil). The experiment was conducted for 10 years on a SOCOCO® Farm and used a randomized block design with three re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Applying diverse chemical fertilizers continuously in elds adversely impacts crops and soil (Lins et al 2021). Due to the prolonged use of inorganic fertilizers, the soils of Coconut elds have started showing a loss of fertility and productivity (Nirukshan et al 2016) in many Asian countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying diverse chemical fertilizers continuously in elds adversely impacts crops and soil (Lins et al 2021). Due to the prolonged use of inorganic fertilizers, the soils of Coconut elds have started showing a loss of fertility and productivity (Nirukshan et al 2016) in many Asian countries.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, continuous monitoring of K in palm elds is necessary to ensure the sustainability of Coconut productivity in the region. It is well-known that excessive use of K in the palm elds can contribute to Magnesium de ciency through antagonism(Lins et al 2021), which needs further investigation. The correlation analysis revealed that SAK in the Coconut elds of Kerala shows a positive correlation with FWC, TOC, SAN, and SAP.…”
mentioning
confidence: 99%
“…Coconut (Cocos nucifera L.) cultivation is an economically important agricultural activity in Brazil (Lins et al, 2021). The state of Ceará is the largest national producer, followed by Bahia, Pará, and Sergipe (IBGE, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Mineral fertilization is used to promote growth and increase crop yield (Lins et al, 2021). For dwarf varieties, the need for fertilization is even greater because they extract more nutrients from the soil than traditionally cultivated genotypes (Teixeira et al, 2005).…”
Section: Introductionmentioning
confidence: 99%